Fungsi Rima dalam Lirik Lagu - Muhamad Hermintoyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The lyrics of a song as a creative piece of poetry are made up of physical and mental elements. Physical elements include diction, image, rhetorical means, and rhyme, while the inner element is the meaning. Rima or poetry in the lyrics (poetry) in addition to acting as aesthetics also provides a comfortable atmosphere, fun called eufofoni sound and provide euasana otherwise called kakophoni. Eufofoni sounds in the form of vowel sound, while the sound of kakofoni in the form of consonant sound. The sounds are deliberately chosen by the author as a means of rhetoric to be enjoyed in accordance with the meaning and theme contained in the lyrics. Rima in the lyrics (poetry) aesthetically gives the neatness of sound at the end of the stan neatly with the pattern aaaa (full), abab (cross), abba (hug), aabb (spouse) and broken (abcd).